Kinematics and Temperature Structures of Filaments in Serpens Main and Serpens South - Lee, Katherine (2014)
We present a study of filaments in Serpens Main and Serpens South cluster regions based on N2H+(1-0) observations from the CARMA Large Area Star-formation Survey (CLASSy) and dust continuum images from the Herschel Space Observatory. Serpens Main and Serpens South are active star formation regions with prominent filamentary structures; however, the role of the filaments in the cluster formation is unclear. This study of filament structure and kinematics with high-angular resolution data (7 arcsecs), particularly in revealing possible infall signatures, provides physical insight to this question. Using the Herschel data, we estimate the temperature in and along filaments for comparison with their gas kinematics, spatial distribution, and N2H+(1-0) emission, to better understand their role in current star formation activities.